Factores que inciden en los embarazos de las adolescentes y su relación con el rendimiento académico, en la Unidad Educativa Nicolás Infante Díaz, período 2014. - Rosero Pincay, Inés del Pilar (2015)
The research was conducted at the Education Unit "Nicolas Diaz Infante" at the Parroquia San Camilo Street between Route 101 Bolivia and Brazil to Babahoyo. It lasted 90 days. The methodology used in this research was to determine the factors involved in teen pregnancy and its relationship with academic achievement. The methods used were: scientific, historical logical, hypothetical deductive, inductive, deductive, descriptive and statistical. The research was quantitative documentary and experimental. The study population was determined in all pregnant teenagers. The techniques and instruments were: direct observation work continuous field to determine the facts involved in this phenomenon also was used to review the minute books of scores of pregnant teenagers, surveys contributed to obtain accurate information and key from the total number of pregnant teenagers.